The Influence Of Solvatibility Ration, Company Size, TATO, ROA, DER On Return Price Of Properties Subsectors In 2019-2021 - Firda Farhany Dimyati (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this paper is to analyze the effect of solvency ratios, firm size, total turnover (TATO), return on equity (ROA) and debt-to-equity ratio (DER) on company performance/share prices in real terms. in the real estate subsector. 2019-2021 The purpose of this research is to understand the factors affecting the stock price of real estate. The research method is panel regression analysis, which uses secondary information obtained from the financial statements of listed real estate companies. The research sample consists of several companies in the real estate subsector covering a certain period. The results of the present study show that the solvency ratio, firm size, TATO, ROA and DER significantly affect the performance/share price of companies in the real estate sub-sector. Importance ratios, firm size, and ROA positively affect stock return/price, while TATO and DER affect negatively. This shows that investors tend to pay attention to these factors when evaluating the performance of real estate and determining stock prices. This study helps to understand the factors influencing the performance/share price of companies in the real estate sub-sector. The results of this study can be used as a benchmark for investors, company management and regulatory authorities in making investment decisions and policies related to real estate.